Livestock feed resources: Current production and management practices in central and northern rift valley provinces of Kenya - Lukuyu, Ben A.; Franzel, Steven; Ongadi, P.M.; Duncan, Alan J. (2011)
Smallholder dairy farmers in developing countries face many feed constraints such as inadequate feed quality and quantity, poor storage facilities for feed conservation as well as insufficient water. However, feeding of livestock continues to pose many problems due to lack of information on composition and utilization of locally available feed resources. These problems are aggravated by lack of access to and high cost of feed inputs. The use of cheap and readily available local feed resources has great potential to increase livestock productivity. The East African Dairy Development project in Kenya, through use of various participatory rapid appraisal tools conducted a rapid appraisal study of three project areas. The objective was to assess feeds and feeding practices in smallholder dairy systems, identify feed resources available year round and where the gaps are as well as to determine what practices are available for improving production and utilization of feed resources in order to raise smallholder dairy production.